Subject to truth: before and after governmentality in Foucault’s 1970s - Legg, Stephen (Sage, 2016)
In this paper I situate Foucault’s governmentality analytics between his first lecture course (On the Will to Know, 1970-71) and his first course after his two “governmentality” lectures (On the Government of the Living, 1979-80). The lectures are interconnected by a shared interpretation of Sophocles’ Oedipus Rex as well as by different but related obsessions with the production of truth: the earlier, with truth as fact; the latter, with truth as self-relation. The former analyses discourses of truth, law, inquiry and sovereignty in ancient Greece. The latter focuses on early Christian individual manifestations of truth (baptism, penance, and spiritual direction) forming a genealogy of confession and, Foucault suggests, of western subjectivity itself. This paper uses the analytical categories of governmentality, usually used to analyse regimes of government, to perform a comparative reading of the lecture courses, charting the continuities and ruptures in their various studies of episteme, techne, identities, ethos and problematisations. This suggests that the earlier lectures outline the birth of the sovereign-juridical compact that modern governmentalities would emerge through and against, while the later lectures use the term “governmentality” less, but enable the analysis of the conduct of conduct to progress to the ethical scale of self-formation.